PENGARUH DESAIN PRODUK, KUALITAS PRODUK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA KAMPUNG BATIK WIRADESA, KABUPATEN PEKALONGAN - Made Laksmi Saraswati; Ari Pradhanawati; Wahyu Hidayat (Jurnal Ilmu Administrasi Bisnis, 2015)
Along with the times, the competition of UKM is getting tougher so that requires every manufacturer to be able to increase the demand for its products. Batik is a cultural heritage that is born as an art work that continues to evolve along with the times and needs to be preserved. Pekalongan batik industry has good potential and continues to grow. However, during the year of 2009-2013 sales results in Wiradesa batik industry, Pekalongan fluctuated. If this is not resolved then feared Wiradesa batik industry cannot develop so it cannot compete with other batik industry.The purpose of this research is to recognize and explain the influence of product design, product quality, and price towards purchase decision of Kampung Batik Wiradesa, Pekalongan District. This research is explanatory research type approach uses towards towards 97 respondents with a sampling technique accidental sampling. Type of data collection of this study are using the technique of questionnaires, interviews, observation and literature methods.The analysis technique used was qualitative and quantitative. Quantitative analysis using cross-tables, test validity, reliability test, determination coefficient, correlation coefficient, a simple linear regression, multiple linear regression and test of significance (t-test and F-test) and also use the help application programs SPSS 20.0 for Windows.Results of statistical analysis known partial effect between product design towards purchase decision by 25,3%, product quality towards purchase decision by 33,8% and price towards purchase decision by 39,4%. The simultaneous influence of product design, product quality and price on purchase decision is 45,2% and 54,8% is affected by other factors.From these results it can be concluded that the product design, product quality, and price, has influence on purchase decisions either partially or simultaneously. Based on these conclusions, then owner of the UKM need to pay attention to the things about product design development to be more varied in style, color and model, improve the quality of the products offered, as well as give the price according to the quality of the product.